A thematic contribution to humanistic in nursing research: Culture of cares - José Siles González (Universidad de Alicante, 2012)
This work has the objective of describing the context in which the journal Cultura de los Cuidados is born. Also, the influence that international and national journals of humanistic topic has in this fact is valued.